Biologi ngengat Galleria mellonella (Linn.) (Lepidoptera: Pyralidae) pada beberapa jenis pakan buatan - Nadzirum Mubin; Mohammad Riza Krisnadi; Teguh Santoso; Fitrianingrum Kurniawati (Jurnal Entomologi Indonesia, 2022)
The greater wax moth (Galleria mellonella (Linnaeus)) is one of Asia’s most essential pests in honey beekeeping. Apart from being a pest, G. mellonella was also used as a test insect in several business fields. The needs of the population of G. mellonella encourage several areas of the business to cultivate it practically and economically. This study aimed to determine and examine the composition of food ingredients as an artificial diet that can affect the growth and development of G. mellonella. The test consisted of four different feed-modified formulas, namely P1 (corn flour, wheat, glycerol, and yeast), P2 (rice flour, wheat flour, wheat bran, glycerol, and yeast), P3 (wheat flour, wheat, glycerol, and yeast), and P4 (brown rice, glycerol, and yeast). The observation criteria were life cycle, mortality rate, fecundity, and egg fertility of the G. mellonella moth. Based on the study’s results, the life cycle development of G. mellonella was the shortest in the P3 treatment (71.5 ± 5.2 days) and the longest P4 treatment (84.2 ± 8.3 days). The highest mortality rate was in the P3 feed type at 13.12%, while the lowest occurred in the P4 treatment at 4.44%. Based on the fecundity of female imago, treatment P4 had the highest fecundity level of 527.7 eggs/female, while treatment P1 was the lowest (169.6 eggs/female). P4 treatment responded best to several biological aspects of the G. mellonella moth, such as larger body size, lower mortality, and high fecundity rates.